Precede Proceed Faktor Ketidaklengkapan Pengisian Mechanism Of Injury Pada Ringkasan Keluar Pasien - Ni Putu Linda Yunawati; Irma Ultimaningsih; Dara Hastarin; Chistina Ayu Dewi Anggraeni; Vina Shabrina; Dinar Neynda Maharani; Kristin Desi Rahayu; Ni Komang Muryati; Ayu Prastikiswara; Ni Made Indira Sari (Politeknik Negeri Jember, 2023)
The content of medical records is a reflection the quality hospital services so that the incompleteness of medical records can have a bad impact on the health care process to patients. The discrepancy in the writing of the MOI by the PPA with the information on the police report regarding the chronology of the trauma incident resulted in difficulties for coding officers in determining into ICD-10 code for the 4th and 5th characters. This study aims to determine the precede proceed factor affected the incompleteness MOI. This research is a qualitative descriptive with a cross-sectional research design using PRECEDE PROCEED model. The results were obtained based on predisposing factors that the level of DPJP discipline is still lacking so that monitoring and evaluation need to be carried out. Enabling factors caused by interface need to be revised it is necessary to compile an input and output interface design. Reinforcing factors are caused by the absence of a policy governing the filling of MOI, so it is necessary to draft a policy for filling in MOI on medical record files. Optimization efforts for the completeness the MOI is designing a draft policy for filling in the MOI and optimizing monitoring evaluation.